ESTIMATES OF THE STOCKS OF OIL SARDINE AND MACKEREL IN THE; PRESENT FISHING GROUNDS OFF THE WEST COAST OF INDIA - Sekharan, K V (Indian Journal of Fisheries, 2011)
During last decade the oil sardine fishery recorded remarkably high patcheson the west coast. On the other hand, the mackerel fishery declined steeply inthe nineteen-sixties, touching the lowest known levels, in contrast to most otherfisheries of the west coast. The percentage of oil sardine in the all India marinefish landings was 32 in 1968, as against 16 in 1958, the corresponding valuesfor mackerel being 2 and 16. This has focussed attention on the need for quickestimates of the maj;mtude of these populations. One approach for this wouldbe to survey the areas occupied by these two species through acoustic and othermeans. Another approach would be to use the known population parametersand mathematical models to yield estimates of the populations. The latter methodis adopted here.